Clinicopathologic significance of heat shock protein 60 as a survival predictor in breast carcinoma - Wang, Qing; Chen, Shengzhou; Wu, Zhihong; Ni, Jungang (Frontiers in Oncology, 2024)
Background: While Heat Shock Protein 60 (HSP60) has been linked to human tumour, its clinic significance specifically in breast carcinoma is unclear. This investigation aims to retrospectively evaluate how HSP60 protein levels relate to survival outcomes among patients diagnosed with breast carcinoma. Methods: Evaluation of 206 patients diagnosed with breast carcinoma and receiving treatment from January 2012 to April 2018, carried out retrospectively. The protein level of HSP60 in breast carcinoma determined by immunohistochemical. Results: The study provided evidence of a distinct upregulation of HSP60 expression in breast carcinoma tumour samples in contrast to adjacent normal tissue samples. Additionally, heightened HSP60 expression was linked to advanced T stage (P = 0.046), N stage (P = 0.034), tumour metastasis (P = 0.016), pathological grading (P = 0.012), and adjuvant therapy utilization (P = 0.004). Moreover, elevated levels of HSP60 proteins exhibited a significant inverse correlation with overall survival (OS) [hazard ratio (HR) 1.598, P = 0.018] and progression-free survival (PFS) (HR 1.600, P = 0.017) among breast carcinoma patients in univariate analyses. The results of multivariate analyses highlighted HSP60 may serve as an independent predictor for both OS and PFS in breast carcinoma patients (HR 1.525, P = 0.034; HR 1.528, P = 0.033, respectively). Conclusion: The involvement of HSP60 in breast carcinoma progression suggests its potential clinical relevance in treatment target validation and prognostic assessment of the disease.